DESIGN AND ANALYSIS OF SABOT STRUCTURE OF THE COORDINATOR - WANG ZhenRong; GAO YueFei; LIU HaiTao; LIU Song (Jixie qiangdu)
This paper introduces the structure and working principle of a device for supporting bomb with the combination of ratchet and crank-slider. The virtual prototyping technology is used to analyze the working process of the device,and that the dynamic relationship between the components and the curve of spring force in the buffer mechanism is obtained. The results show that it is feasible to apply the one-way rotation characteristic of ratchet wheel and the quick-return characteristic of crank-slider mechanism to the device. The device for supporting bomb with the principle can realize the cushioning and the locking positioning of the projectile. It meet the projectile transport stability requirements. The device shows the features of intensive structure,small occupied space and wide applicability. It provides a new design idea for the design of the sabot device. While in the mechanical field,it also has a positive significance for extending the scope of combination organization.